Macrocystic serous cystadenoma of the pancreas: Report of 4 cases. (September 2015) - Pravisani, Riccardo; Intini, Sergio Giuseppe; Girometti, Rossano; Avellini, Claudio; Leo, Cosimo Alex; Bugiantella, Walter; Risaliti, Andrea
Abstract: Background: Macrocystic serous cystadenomas (MaSCA) are rare benign tumor of the pancreas which represent an atypical macroscopic morphologic variant of serous cystadenomas (SCA). They are characterized by a limited number of cysts with a diameter of >2 cm and share imaging features overlapping those of mucinous cystic neoplasm (MCN) and branch-duct intraductal papillary mucinous neoplasm (BD-IPMN), thus frequently making the pre-operative radiologic diagnosis difficult. Materials and methods: Four cases of MaSCA, which were surgically treated in our structure, are reported. Results: Two women (62 and 39 year-old) presented with upper abdominal pain and palpable mass underwent CT with evidence of a lobulated cystic neoformation (98 × 70 and 94 × 75 mm respectively) originating from the body and the tail of the pancreas respectively. They underwent distal pancreatectomy for suspected MCN. A 38 year-old woman underwent laparoscopic distal pancreatectomy because of the incidental finding of an unilocular cystic lesion in the pancreatic tail (23 mm) of indeterminate origin (MCN, SCA or metastasis). In a 40 year-old woman, admitted for acalculous acute pancreatitis, an unilocular cystic lesion in the body of the pancreas (62 mm) was detected and confirmed after 2 months at CT, therefore she underwent distal pancreatectomy for suspected pseudocyst or SCA. In all of the 4 patients the histological examination of the specimens revealed a MaSCA. Conclusion: Imaging techniques have a low diagnostic power in terms of differentiation of MaSCA from malignant lesions (as MCNs and BD-IPMN). In the clinical practise of MaSCA, surgery appears to gain indications that are wider than those correlated to the pathologic outcome, because of the necessity of a correct differential diagnosis from potentially malignant cystic tumors and the frequent symptoms requiring treatment.